Beyond Hypertension: Potential Use of “Sartans” in Neurodegeneration, Addictions, Viral and Vaccine Sequelae - Sfera, Adonis (Disease and Health Research: New Insights Vol. 5, 2024)
Like the previous pandemics, COVID-19 has been succeeded by well-documented post-infectious and post-vaccination sequelae. The circulating Spike antigen, acquired either via SARS-CoV-2 infection or mRNA therapeutics, likely drives cardiovascular and thrombotic injuries as well as cognitive and motor dysfunction. This “spike effect” has been positively correlated with angiotensin II (ANG II) upregulation, caused by the S antigen binding angiotensin-converting enzyme 2 (ACE-2), disabling this protein. ACE-2 deficiency causes an imbalance between the horizontal and vertical branches of the renin-angiotensin system (RAS) manifested by elevated ANG II levels. In return, ANG II, a mitochondrial toxin, triggers premature cellular, including neuronal, senescence, promoting cognitive, premotor, and motor pathology. The blood-brain barrier (BBB)-crossing, candesartan has shown beneficial effects in viral infections, neurodegeneration, and substance use disorders, suggesting that repurposing of this agent could avert the “spike effect”. In this perspective article, a look at angiotensin II receptor blockers, “sartans”, alone or in combination with angiotensin (1-7) agonists has been given, as potential treatment modalities for COVID-19 and its sequelae as well as Parkinson’s disease.